A Bidirectional LCC-S Compensator on Wireless Power Transfer with Constant Voltage - Saranyoo Songcharoentrap; Koson Trachu; Worapong Pairindra; Surin Khomfoi (My University, 2025)
This paper studies a bidirectional wireless power transfer (BD-WPT) system designed for electric vehicles (EVs) operating at 400V input, 350V output, 11kW, and 85kHz. The bidirectional power electronic devices that function as inverters or rectifiers with relays are employed to alter the direction of power flow between the source and the vehicle in the bidirectional DC-DC converter, which utilizes the LCC-S resonant circuit that is designed separately for the source and vehicle. MATLAB/Simulink is used to conduct the validation. The output voltage on both the source and the vehicle sides can be regulated to a specific level.
Keywords: Wireless Power Transfer Systems; Energy Harvesting in Wireless Networks; Advanced Battery Technologies Research